Enacted learning through CALL software : an investigation into adapting available CALL software to meet students' needs - Hanita Hassan ([s l] : Aston University, 1993)
Call software is an interesting tool for language learning. However, the software, which is produced for commercial purposes, does not fulfil students needs.As a result, students found that CALL is unable to assist them in language learning.This study tries to find ways to adapt the available CALL software to meetstudents' needs. Students' real-world materials are employed and exercises in the software are adapted in order to enable students to accomplish real-world communication. Students are required to give feedback on which typeof software do they prefer.The study finds that both types of software - unadapted and adapted, arepreferable. Both types of software are able to assist students in languagelearning in different ways.